Impact of Ticagrelor vs. Clopidogrel in Patients With Acute Coronary Syndrome Undergoing Left Main Percutaneous Coronary Intervention - Miaohan Qiu; Xuehan Zhi; Haiwei Liu; Zhenyang Liang; Bin Wang; Kai Xu; Shaoyi Guan; Geng Wang; Xiaozeng Wang; Yingyan Ma; Quanmin Jing; Xiaoxia Fu (Cardiology Discovery)
Abstract. Objective:. There is limited evidence regarding the choice of P2Y12 receptor inhibitors as a component of dual antiplatelet therapy in patients with left main (LM) disease undergoing percutaneous coronary intervention (PCI). This study aimed to evaluate long-term clinical outcomes of ticagrelor- vs. clopidogrel-based dual antiplatelet therapy strategy in acute coronary syndrome (ACS) patients undergoing LM PCI. Methods:. This is a post-hoc analysis from a prospective, single-center, real-world PCI registry. A total of 1,163 patients discharged post-ACS who underwent LM PCI and received ticagrelor or clopidogrel between March 2016 and March 2019 were included in the study. The primary endpoint was ischemic events at 12 months, including cardiac death, myocardial infarction, or stroke. Secondary outcomes included all-cause death and Bleeding Academic Research Consortium types 2, 3, and 5, and types 3 and 5 bleeding. Propensity score matching was used to adjust for bias due to confounders between the 2 groups. Results:. The ticagrelor and clopidogrel groups comprised 529 (45.49%) and 634 (54.51%) patients, respectively. During the follow-up period, the rate of ischemic events was significantly lower with ticagrelor than with clopidogrel before (1.32% (7/529) vs. 3.63% (23/634), P = 0.013,6) and after propensity score matching (1.41% (6/425) vs. 4.00% (17/425), P = 0.020,1). The rates of all-cause death, Bleeding Academic Research Consortium-defined type 2, 3, and 5 bleeding, and type 3 and 5 bleeding were similar between the ticagrelor group and clopidogrel group before or after propensity score matching adjustment (all P > 0.05). Conclusion:. Among patients with ACS undergoing LM PCI, ticagrelor use was associated with ischemic events benefit without excessive risk of bleeding at 12 months compared with clopidogrel.